طبخ السكر في مصر المملوكية - مصطفى، محمد السيد (جامعة عين شمس - كلية الآداب, 2018)
تم في هذا البحث دراسة طبخ السكر في مصر المملوكية وتم تقسيمه إلى: 1) مطابخ ومعاصر السكر: حيث احتلت معاصر السكر في العصر المملوكي مكانة كبيرة لما كانت تنتجه من كميات كبيرة من السكر وقد ذكر لنا بعض المؤرخين المعاصرين مثل ابن دقماق العديد من معاصر ومطابخ السكر، كما تم وصفها من خلال وصف معصرة السلطان المؤيد ببولاق، كما ذكر الرنوك التي حرص المماليك على وضعها على مطابخ ومعاصر السكر وأسعار بيع بعض معاصر ومطابخ السكر، وكيف تدنى سعرها في نهاية العصر المملوكي بسبب سياسة الاحتكار التي اتبعها السلاطين التي ضيقت على أصحاب المعاصر والمطابخ، فباعوها بأسعار زهيدة. 2) مراحل طبخ السكر: قد مر طبخ السكر بستة مراحل تم اتباعها في جميع المعاصر والمطابخ خلال العصر المملوكي، فكانت المرحلة الأولى نقل عيدان القصب إلى دار القصب وتنظيفه، والمرحلة الثانية نقل القصب بعد تنظيفه لبيت النوب وفيه يقطع القصب إلى قطع صغيرة، وفي المرحلة الثالثة يتم عصر قطع القصب، أما المرحلة الرابعة تجمع عصارة القصب وتصفى، والمرحلة الخامسة يطبخ العصير على النار، وفي المرحلة السادسة يتم تكرير السكر ليصل إلى البياض. 3) عمال وموظفي الإشراف على السكر: تعدد عمال وموظفي الإشراف على السكر ومطابخه بداية من العصار والطباخ إلى ناظر مطابخ السكر، والمحتسب الذي باشر وراقب طبخ السكر وباشر سوقه وراقب أصحاب الحرف التي قامت على السكر كالحلوانين والشرابين وبائعي الأدوية، كما باشر عمال الشراب خاناه وشاد الشراب خاناه والحوائج خاناه المشربات والرواتب من السكر الحلوى، وكان لهؤلاء العمال موظف عام عرف بالاستادار الذي كان مسئولا عن أمر البيوت السلطانية وما تحتاجه من سكر وغيره.
in it sugar cooking was studied in Mamluk Egypt and was divided into: (1) kitchens and sugar refineries: as the sugar refineries in the Mamluk era had a great place for the production of large amounts of sugar and some contemporary modernists such as Ibn Daqmaqmentioned to many contemporary and sugar kitchens, as described through the description of the Sultan Al-Muayadrefinery in Bulaq, He also mentioned the Rnok, which the Mamluks were keen to put on the kitchens and sugar refineries and the prices of the sale of some of the refineries and sugar kitchens, and how the price dropped at the end of the Mamluk era because of the monopoly policy adopted by the sultans, which made the owners of refineries and kitchens suffer a lot , so they sold them cheaply. (2) The phases of sugar cooking: The sugar cooking passed through six phases which were applied in all refineries and kitchens during the Mamluk era. The first stage was the transfer of sugar cane sticks to the reed house and cleaning it, the second phase, the reeds were transferred after cleaning to the house of the nob and cutting the canes into small pieces. in the third phase the cane cut was pressed ,in the fourth phase the reed and reed sab is filtered , and in the fifth phase juice is cookedon fire, and in the sixth phase sugar is refined to reach the bleach . (3) workers and employees supervision of sugar: the workers and employees supervision of sugar and its kitchens ranged from the presser , the cook to the head of the sugar kitchens, and El Mohtaseb who controlled and watched the cooking sugar and shared in it marketing and watched the owners of the crafts that were based on sugar like patisseries and sweet drinkers and the seller of medicines, and watched drink workers ( khanah) was drunk shad ( khanah) and the beneficiaries ( khanah) and the salaries of sugar and candy, and these workers had a public servant known as Astadar, who was responsible for the sultanihouses and the need for sugar and others.
Keywords: الدولة المملوكية -- معاصر السكر -- التاريخ الاسلامى -- مصر